Profil tekstur dan warna getuk dengan variasi lemak padat - Muhammad Iqbal Fanani Gunawan; Soraya Kusuma Putri; Rizka Qurrota A'yun (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Getuk is an Indonesian food made from cassava, which is steamed and then mashed finely and topped with grated coconut. Research on getuk in Indonesia is currently minimal. Solid fats like margarine and butter have been proven to improve the quality of bread products. Getuk is divided into 6 treatments, including control treatment and a combination of solid fats such as butter, and margarine. The analyses conducted include texture profile, color, and moisture content. The addition of solid fats has been shown to have a significant difference in the texture parameters of Hardness, Gumminess, and Chewiness, but it did not have a significant effect on the Resilience parameter. The combination of butter and margarine resulted in a significant decrease in the Springiness and Cohesiveness parameters. Overall, the addition of solid fats had an impact on increasing brightness (L*) and shifting the color towards yellow tendencies (positive b*). The addition of solid fats did not significantly affect the moisture content of getuk.